Tree Stand Structure of Surili (Presbytis comata) Habitat in the Abi-Karna Forest Block, Tea and Cinchona Research Center, Gambung, Bandung Regency, West Java - Feriska Lindayu; Marcelita Putri Utami; Salsa Mumtaz Saidatinah; Syivaul Jannah AH; Akhmad Rudini; Sri Suci Utami Atmoko (Universitas Nasional Jakarta, 2026)
Primates play a crucial role in forest conservation through seed dispersal from the fruits they consume. Factors influencing primate presence in their habitat include food availability, the presence of predators, and human activity. This study aimed to analyses the tree stand structure of the surili habitat in the Abi-Karna Forest Block, PPTK-Gambung, Pasir Jambu, West Java. The study was conducted over three days, from May 2-4, 2024, using the line transect method. Parameters measured included the number of trees, tree height (h), stem diameter (cm), crown thickness, crown curvature, and crown width diameter. Data analysis included relative density index, dominance, and tree species diversity. The results showed differences in tree stand structure between the western and eastern zones of the Abi-Karna Forest. The western zone had a higher tree species diversity than the eastern zone, with 2,022 and 1,612, respectively. The dominant tree species in both zones were Rasamala and Puspa. Tree heights in the western and eastern zones were 16-20 m, while tree DBH was 10-30 cm. The dense forest canopy plays acrucial role in providing primary food sources and maintaining ecosystem health. The dense canopy cover in the western zone is more conducive to surili activity than in the eastern zone. The tree stands in the Abi-Karna Forest provide food sources, shelter, and movement routes for surili (Presbytis comata) and other primates, such as the Javan langur (Trachypithecus mauritius), found in the area